Effects of Local Spices on the Utilization of Cassava Peel Meal-Based Diets by Weaner Rabbits - Okoye, F.C.; Ugwuene, M.C.; Mbarah, J.U. (Pakistan Journal of Nutrition, 2006)
The performance of weaner rabbits fed diets containing Monodora nyristica Spice , Zingiber official (ginger spice) and Cocos nucifera (coconut spice) respectively was compared with that of weaner rabbits fed diet that did not contain any of the spices to ascertain the influence of spices on the utilization of cassava peel meal. Four diets 1, 2, 3 and 4 were formulated with diet 1 (control) containing no spice while diets 2, 3 and 4 contained Monodora myrsitica, Zingiber ans Cocos nucifera soices respectively. The experiment was a completely Randomized Design with four treatments and two replicates each. Thirty-two weaner rabbits (New Zealand White X Chinchilla) were used with four rabbits per replicate and eight per treatment in the experiment which lasted eight weeks. The final body weight, and weight gain of rabbits fed Zingiber officinal spice diets were significantly higher (P< 0.05) than the other diets (1, 2 and 4). The feed intake of the diets containing the spices (diets 2, 3 and 4) was significantly higher (p< 0.05) than diet 1 (control) which had no spice. This shows that the spices made the diets more palatable than the diet without spice. The feed conversion ratio of rabbits fed the diet containing Zingiber officinal spice was significantly better (p< 0.05) than others. The hemoglobin and packed cell volume content of the blood of rabbits fed Zingiber officinal spice were significantly higher (p< 0.05) in the percentage dressed weight and erum cholesterol contents of the rabbits fed all the treatment diets. For economics of production, the diet containing Monodora myristica recorded the highest cost per kg feed whereas the containing Zingiber officinal had the highest cost per kg weight gain. Spices especially ginger spice enhanced the utilization of cassava peel meal.